Transformation of Religious Values in Lampung Community Culture - Anggi Novita Sari; Ilim Abdul Halim (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the relationship between Islamic teachings and the local wisdom of the Lampung community, focusing on the transformation of religious values within socio-cultural life. Lampung has a traditional value system, including piil pesenggiri, nemui nyimah, nengah nyappur, and sakai sambayan, which shapes the social identity of its people. In the modern context, these values undergo reinterpretation alongside the development of Islamic da'wah, education, and digital media. Using a sociology of religion approach, this study examines how Islam adapts to local wisdom without compromising the substance of its teachings. The analysis is carried out using Clifford Geertz's theory of religion as a cultural system, as well as Ernest Gellner's theory of the tension between normative Islam (ulama) and local Islam (the people). The results of the study show that the integration of Islam and Lampung customs produces an inclusive and harmonious form of religiosity, as well as a model of Islam typical of the archipelago that can withstand the currents of modernization and globalization.